Splenectomy as Flow Modulation Strategy and Risk Factors of De Novo Portal Vein Thrombosis in Adult‐to‐Adult Living Donor Liver Transplantation. Issue 9 (24th September 2018) - Linares, Ivan; Goldaracena, Nicolas; Rosales, Roizar; Maza, Luis De la; Kaths, Moritz; Kollmann, Dagmar; Echeverri, Juan; Selzner, Nazia; McCluskey, Stuart A.; Sapisochin, Gonzalo; Lilly, Leslie B.; Greig, Paul; et al.
Abstract : Portal vein thrombosis (PVT) is a severe complication after liver transplantation that can result in increased morbidity and mortality. Few data are available regarding risk factors, classification, and treatment of PVT after living donor liver transplantation (LDLT). Between January 2004 and November 2014, 421 adult‐to‐adult LDLTs were performed at our institution, and they were included in the analysis. Perioperative characteristics and outcomes from patients with no‐PVT (n = 393) were compared with those with de novo PVT (total portal vein thrombosis [t‐PVT]; n = 28). Ten patients had early portal vein thrombosis (e‐PVT) occurring within 1 month, and 18 patients had late portal vein thrombosis (l‐PVT) appearing later than 1 month after LDLT. Analysis of perioperative variables determined that splenectomy was associated with t‐PVT (hazard ratio [HR], 3.55; P = 0.01), e‐PVT (HR, 4.96; P = 0.04), and l‐PVT (HR, 3.84; P = 0.03). In contrast, donor age was only found as a risk factor for l‐PVT (HR, 1.05; P = 0.01). Salvage rate for treatment in e‐PVT and l‐PVT was 100% and 50%, respectively, without having an early event of rethrombosis. Mortality within 30 days did not show a significant difference between groups (no‐PVT, 2% versus e‐PVT, 10%; P = 0.15). No significant differences were found regarding 1‐year (89% versus 92%), 5‐year (79% versus 82%), and 10‐year (69% versus 79%) graft survival between the t‐PVT and no‐PVT groups, respectively ( P = 0.24). The 1‐year (89% versus 96%), 5‐year (82% versus 86%), and 10‐year (79% versus 83%) patient survival was similar for the patients in the no‐PVT and t‐PVT groups, respectively ( P = 0.70). No cases of graft loss occurred as a direct consequence of PVT. In conclusion, the early diagnosis and management of PVT after LDLT can lead to acceptable early and longterm results without affecting patient and graft survival.